Phytoremediation of cadmium contaminated soils by Amaranthus Hypochondriacus L.: The effects of soil properties highlighting cation exchange capacity. (November 2021) - Cui, Xiaoying; Mao, Peng; Sun, Shuo; Huang, Rong; Fan, Yingxu; Li, Yongxing; Li, Yingwen; Zhuang, Ping; Li, Zhian
Abstract: Phytoremediation is a cost-effective method to remedy Cd-contaminated soils. However, it is difficult to predict the performance of a given (hyper)accumulator at different soils due to the divergent plant-soil mutual fitness. Soil properties could be quite influential in determining plant growth and Cd uptake and therefore affect phytoremediation efficiency. To explore the primary soil factors that regulate the efficiency of phytoremediation, a phytoextraction experiment with grain amaranth ( Amaranthus Hypochondriacus L.) was conducted in six long-term Cd-contaminated agricultural soils from southern China. The results showed that besides the soil available Cd, the soil cation exchange capacity (CEC) greatly affected plant growth and the amount of total Cd extraction. The deficiency of available Ca and Mg in low CEC soil caused insufficient uptake of Ca and Mg by grain amaranth, which was adverse to plant growth and Cd detoxification. The impaired plant biomass production sharply influenced plant total Cd accumulation, despite the relatively high Cd concentration in plants. While for the grain amaranth grown in soils with higher CEC, the increases in plant Ca and Mg promoted plant photosynthesis and plant tolerance to Cd stress, as indicated by the increase of leaf chlorophyll content and antioxidant enzyme activities, which contributed to the higher plant biomass and phytoremediation efficiency. These findings highlight that maintaining regular plant biomass production is vital to ensure the efficiency of phytoremediation, and low CEC of soil is a substantial barrier that needs to be concerned and further addressed for efficient phytoremediation of Cd-contaminated soils. Highlights: A phytoextraction experiment was conducted in six Cd-contaminated field soils. Primary soil factors regulating the efficiency of phytoremediation were identified. Low CEC soils deficient in Ca and Mg impaired phytoremediation efficiency. Insufficient uptake of Ca and Mg hindered plant growth and Cd detoxification. Maintaining regular plant biomass production is vital for efficient phytoremediation.